REKONSTRUKSI STRUKTUR KURIKULUM PENDIDIKAN AGAMA ISLAM DI MADRASAH DALAM MENJAWAB TANTANGAN PENDIDIKAN KONTEMPORER - Manan, Abdul; Faruqi, Adnan (LP2M Universitas Ibrahimy, 2025)
Educational transformation in the contemporary digital era, marked by globalization and rapid technological advancement, demands an adaptive, integrative, and contextual curriculum. In the context of madrasahs, the Islamic Religious Education (PAI) curriculum is required not only to preserve Islamic values but also to address challenges in digital literacy and social dynamics. This study aims to examine the alignment of the PAI curriculum structure in madrasahs with the demands of the contemporary digital era. This research employs a literature review, analyzing relevant scientific journals, academic books, and research articles. The findings indicate that the existing PAI curriculum structure in madrasahs remains fragmented, with limited integration among PAI subjects and insufficient alignment with the competencies required in the 21st Century. The reconstruction of the curriculum structure based on integrative principles, contextual learning, and the utilization of educational technology is considered capable of enhancing the effectiveness of PAI learning. This study concludes that reconstructing the PAI curriculum structure is a strategic necessity to strengthen religious character while simultaneously developing students’ competencies in the contemporary digital era.